Prognostic value of atrial fibrillation in patients with heart failure and different left ventricular ejection fraction: results of the multicenter RIF-CHF register - I. V. Zhirov; N. V. Safronova; Yu. F. Osmolovskaya; S. N. Тereschenko (Российский кардиологический журнал)
Heart failure (HF) and atrial fibrillation (AF) are the most common cardiovascular conditions in clinical practice and frequently coexist. The number of patients with HF and AF is increasing every year.Aim. To analyze the effect of clinical course and management of HF and AF on the outcomes.Material and methods. The data of 1,003 patients from the first Russian register of patients with HF and AF (RIF-CHF) were analyzed. The endpoints included hospitalization due to decompensated HF, cardiovascular mortality, thromboembolic events, and major bleeding. Predictors of unfavorable outcomes were analyzed separately for patients with HF with preserved ejection fraction (AF+HFpEF), mid-range ejection fraction (AF+HFmrEF), and reduced ejection fraction (AF+HFrEF).Results. Among all patients with HF, 39% had HFpEF, 15% — HFmrEF, and 46% — HFrEF. A total of 57,2% of patients were rehospitalized due to decompensated HF within one year. Hospitalization risk was the highest for HFmrEF patients (66%, p=0,017). Reduced ejection fraction was associated with the increased risk of cardiovascular mortality (15,5% vs 5,4% in other groups, p<0,001) but not ischemic stroke (2,4% vs 3%, p=0,776). Patients with HFpEF had lower risk to achieve the composite endpoint (stroke+MI+cardiovascular death) as compared to patients with HFmrEF and HFrEF (12,7% vs 22% and 25,5%, p<0,001). Regression logistic analysis revealed that factors such as demographic characteristics, disease severity, and selected therapy had different effects on the risk of unfavorable outcomes depending on ejection fraction group.Conclusion. Each group of patients with different ejection fractions is characterized by its own pattern of factors associated with unfavorable outcomes. The demographic and clinical characteristics of patients with mid-range ejection fraction demonstrate that these patients need to be studied as a separate cohort.